Pengaruh Transparansi, Keterlacakan, Keamanan Data dan Adopsi Inovasi Blockchain Terhadap Kepercayaan dan Kinerja Penanganan Komplain pada PT Pos Indonesia - Dicky Anggriawan; Melia Eka Lestiani; Agus Purnomo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze and verify the influence of transparency, traceability, data security, and Blockchain innovation adoption on customer trust, as well as their impact on complaint-handling performance at PT Pos Indonesia’s Tanjungpandan Branch Office. The study is motivated by issues such as information asymmetry and structural failures in the tracking mechanisms of conventional SAP ERP systems, which have led to a high volume of consumer complaints (YLKI 2025 data) and a low Top Brand Index score of 9.40% relative to competitors. The research employed a quantitative approach combined with an explanatory design. Primary data were collected from 110 respondents selected via purposive sampling, comprising logistics partners, corporate clients, and major retail users. A 1–5 Likert scale was utilized. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), with SmartPLS software employed for the analysis. The results indicate that all 13 hypotheses were accepted, showing positive and significant relationships. Blockchain innovation adoption proved to have the most dominant influence on customer trust (0.386), while traceability emerged as the primary driver for enhancing complaint-handling performance (0.308). R-Square values ​​demonstrate that the model explains 75.1% of the variance in trust and 81.6% of the variance in complaint-handling performance, classifying it as an excellent predictive model. Furthermore, trust was found to partially mediate the relationships between the variables. In conclusion, transitioning to a decentralized digital architecture offers a strategic solution for PT Pos Indonesia to eliminate information asymmetry, restore service credibility, and achieve operational efficiency in resolving customer complaints.